Intersectionalizing the Homogenous Commonplace: Finnish Feminist Party and the Diversification of the Story of Nordic Social Coherence - Ilmonen Kaisa; Rossi Leena-Maija (Brill, 2022)
Intersectionality has been a debated concept in recent critical studies. It has been both hailed as the most important contribution to gender studies, and criticized for being an academic buzzword. In our chapter, however, we aim to focus on the potential productive power intersectionality might still have, for example, when critically applied to the narratives of cultural homogeneity and the ‘ordinariness’ of the majority. The narrative of Nordic societal homogeneity is often constructed as unitary and unchanging – the sphere of the ordinary. The white Nordic majority has become the norm against which the other, presented as in need of emancipation, is defined, read and interpreted. In such thinking, both ‘the majority’ and ‘the margin’ are stabilized constructs, even though they both remain inherently multifaceted and ambivalent. We turn the intersectional lens to the ‘homogenous commonplace’ by discussing on which conditions intersectionality could be turned towards the majority, or ‘the ordinary’. After that, we discuss intersectionality ‘in commonplace action’, by outlining a case study: the explicitly intersectional politics of the Feminist Party in Finland, founded in 2016.
Thinking with the Familiar in Contemporary Literature and Culture 'Out of the Ordinary'